Cash crop choice and income dynamics in rural areas: evidence for post‐crisis Indonesia. (11th April 2013) - Klasen, Stephan; Priebe, Jan; Rudolf, Robert
Abstract In this article we investigate the factors affecting levels and growth of incomes in rural Indonesia following the crisis of 1997–1998. In particular, we investigate the relative roles of nonfarm incomes and productivity improvements achieved via changes in crops versus improvements on the same crops on income dynamics. Framing the article in the context of an optimal labor allocation model, relying on unique household panel data from Central Sulawesi, and using advanced panel econometric methods, we find that local innovations related to the adoption and intensification of new cash crop varieties, more specifically the shift from coffee to cocoa production, can explain a substantial part of the observed post‐crisis developments. Causal estimates of the effect of growing cocoa suggest that households were on average able to achieve about 14% higher income levels during the post‐crisis period compared to the planting of other crops, most notably coffee. Also, our results demonstrate the importance of engagement in nonfarm activities for household income growth. Comparative analyses using a nationally representative survey suggest that similar processes are at play in other parts of Indonesia.